Including learners with low-incidence disabilities - West, Elizabeth A., 1968- (International perspectives on inclusive education ;, 2015)
This Volume focuses on inclusive education for the less than 1 of school-age population who have been diagnosed with Low-Incidence Disabilities and continue to be marginalized in many ways. This unique contribution provides a wide-range of perspectives on what works to facilitate inclusion in a variety of contexts. In many countries teachers are being asked to ensure that all of their students achieve, regardless of background or disability leaving many grappling with how to facilitate inclusion for learners with low-incidence disabilities. The first section of this text presents strategies and supports for inclusion. It offers the reader examples of good practices that practitioners can employ to improve teaching and learning in their school or classroom for these students and their families. The second section offers a range of international perspectives that illuminate the work being done related to inclusion for learners with low-incidence disabilities within those contexts. This important book highlights the need to include learners with low-incidence disabilities and provides information related to supports and services to achieve that goal across a variety of contexts.